Histological Evaluation of Placenta in Relation with Maternal Age in Normal Uncomplicated Pregnancy - Eman Sheet (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Background: The placenta is a fetomaternal structure that determines normal fetal growth and maturation, the function of the placenta depends on the normal differentiation of the villous trophocytoblast and the thickness of the placental barrier. Placental insufficiency associated with abnormal neonatal outcome. The aim of this study is to evaluate thehistological structure of the placenta according to maternal age.Methods: A case control prospective study is done on sixty placentae from women delivered normally at Al-Khansaa obstetric Hospital, the samples of placentae are classified into three groups according to the maternal age: group A: mother age (20-34) years considered as control group, group B: mother age (19-15) years while group C: maternal age35-50. The placentae are weighted and their diameters include thickness, are measured then pieces from placentae are taken to asses oxidative stress biomarker and other pieces are fixed in formalin solution then processed and prepared for light microscopic examination.Results: The mean weight and surface area of placentae of mothers over 35 years were decreased while their thickness increased as compared to that of control and young age group, the oxidative stress biomarker increased in this group whereas the histological study revealed thickening of placental barrier, decreased of villus vascularity, increased villusstroma with fibrinoid deposition and increased syncytial knot.Conclusion: Pregnancies, in advanced maternal age rather than youth, can negatively impact the structure of the placenta due to increased oxidative stress. To potentially help support function in this age group adding antioxidants could be beneficial.